Evidence for powerful winds and the associated reverse shock as the origin of the Fermi bubbles. Issue 3 (12th November 2022) - Fujita, Yutaka
ABSTRACT: The Fermi bubbles are large gamma-ray-emitting structures. They are symmetric about the Galactic Centre (GC), and their creation is therefore attributed to intensive energy injection at the GC. In this study, we focus on the non-equilibrium X-ray gas structures associated with the bubbles. We show that a combination of the density, temperature, and shock age profiles of the X-ray gas can be used to distinguish the energy-injection mechanisms. By comparing the results of numerical simulations with observations, we indicate that the bubbles were created by a fast wind from the GC because it generates a strong reverse shock and reproduces the observed temperature peak there. On the other hand, instantaneous energy injection at the GC cannot reproduce the temperature profile. The wind had a speed of ${\sim} 1000\rm \: km\: s^{-1}$, and blew for ∼10 7  yr. Because the mass flux of the wind is large, the entrainment of interstellar gas by wide-angle outflows from the black hole is required. Thus, the wind may be the same as active galactic nuclei outflows often observed in other galaxies and thought to regulate the growth of galaxies and their central black holes.